On the Work of a Naturalist in South American Forests in the Early 20 Century (Concerning the Article by Ivan D. Strelnikov «In the Forests of Brazil») - E. S. Soboleva (Ибероамериканские тетради, 2025)
Five members of the Second Russian Expedition to South America (1914–1915) spent most of their time there in remote and inaccessible areas. They dreamed of knowing life in the greatest power of its manifestations, in the richness and greatness of forms, colors of the world of plants and animals; they longed to know the origins of the development of human spiritual life getting into contact with primitive tribes in remote areas of the tropical jungle. Naturalists Ivan D. Strelnikov and Nikolai P. Tanasiychuk stayed in Brazil, Bolivia and Paraguay for almost 20 months, sometimes in difficult and life-threatening conditions, conducted scientific research, collecting exhibits for Russian museums. For more than eight months, they worked at the Puerto Bertoni science station in Paraguay. Human survival and adaptation to tropical conditions is a constant topic in their diaries. In Russia, they promoted the continuation of the scientific study of South America. The circumstances of the First World War and the Russian revolution did not allow them to fully process and publish all the results of their ethnographic, zoological and botanical research. Later Ivan D. Strelnikov in the manuscript «In the forests of Brazil» expressed his impressions and delight at the world of the virgin nature of the South American continent. Strelnikov’s diaries, which his family recently sent to the Kunstkamera of St. Petersburg, are published for the first time.